Teachers’ choice of examples and talk in mediating the chosen examples in Grade 8 multilingual classrooms - Kate, Sehowa Mmatsela (University of the Witwatersrand, Johannesburg, 2024)
Examples that teachers of mathematics choose to relay the mathematical narrative to their learners plays a crucial role in the kind of mathematics that learners then have access to (or not). Furthermore, how the teachers bring the chosen examples to life through classroom talk, which aims to mediate the chosen examples is what determines what learners truly learn. Data in the study was collected through consecutive video recordings of lessons during which linear and exponential equations were covered from start to finish and post-lesson interviews with the two teachers. In this study, I have used Essien’s (2021b) Dyadic framework to analyse the findings. One of the interesting findings in the study is that although the two teachers involved teach in the same school, they teach differently, for example, one teacher used talk to mediate the examples through code-switching (to Sesotho and IsiXhosa), while the other teacher strictly used the LoLT (English). Additionally, both teachers allowed their learners to write corrections on the board, which then allowed teachers to conceptualise their learners’ lived object of learning (and whether or not it aligns with the intended object of learning). Through the work learners wrote on the board, teachers were then able to invite mathematical discussions (with the whole class). One other interesting finding is that the teachers dominantly accepted learners’ choral responses which limited prospects for meaningful discussions, which led to missed opportunities for further learning.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; examples; example space; variation theory; choice of examples; meaning making; talk; mediate; multilingual; algebra; equations; linear and exponential equations; code- switching; resources; SDG-4: Quality education